Progress of ISO Standards on the Confinement Systems in Fusion Facilities Using Tritium. (19th May 2017) - Lepetit, L.; Cortes, P.; Thomas, L.
Abstract: This technical note presents progress of a standard developed under the frame of the working group dealing with confinement, ventilation and shielding issues. The current standard ISO 17873 was created for nuclear facility application for which tritium does not represent the main source term. In order to guide guidance to the designers, two criteria based on contamination source term are proposed to classify systems dealing with aerosols or gaseous issues, and technologies in this field are outlined.